How can a high-quality genome assembly help plant breeders?. Issue 6 (10th June 2019) - Benevenuto, Juliana; Ferrão, Luís Felipe V; Amadeu, Rodrigo R; Munoz, Patricio
Abstract: The decreasing costs of next-generation sequencing and the improvements in de novo sequence assemblers have made it possible to obtain reference genomes for most eukaryotes, including minor crops such as the blueberry ( Vaccinium corymbosum ). Nevertheless, these genomes are at various levels of completeness and few have been anchored to chromosome scale and/or are haplotype-phased. We highlight the impact of a high-quality genome assembly for plant breeding and genetic research by showing how it affects our understanding of the genetic architecture of important traits and aids marker selection and candidate gene detection. We compared the results of genome-wide association studies and genomic selection that were already published using a blueberry draft genome as reference with the results using the recent released chromosome-scale and haplotype-phased blueberry genome. We believe that the benefits shown herein reinforce the importance of genome assembly projects for other non-model species.